Late Detection with Claw Hand Deformity in a Leprosy Person: A Case Report - Surender Benedict; Zulkifli Harun (Sumatera Medical Journal, 2026)
Background: Leprosy is a chronic infectious disease caused by Mycobacterium leprae. It remains a major public health problem and is often neglected, especially in remote communities. Objective: This case report describes a patient with late detection of multibacillary leprosy who presented with advanced deformity, and highlights the factors contributing to delayed diagnosis. Methods: A clinical assessment and detailed history were conducted on a 78-year-old man from the Orang Asli community in Pekan, Pahang. The diagnosis was made clinically and later confirmed through a skin slit smear with acid-fast staining. Disability grading was performed according to the World Health Organization criteria. Results: The patient presented with a left claw hand deformity that had progressed for two years without treatment, accompanied by ulceration and sensory loss. He was classified as having grade 2 deformity. Multidrug therapy (MDT) was started promptly at the primary care clinic, and his symptoms improved after treatment initiation. Stigma and low awareness of leprosy were identified as the main factors contributing to the delay in seeking care. Conclusion: This case illustrates the consequences of late detection of leprosy, which can lead to permanent disability. Early recognition and prompt initiation of MDT remain essential to prevent progression and reduce disability, especially in underserved communities.